Observations on the over~·intering and \\'inter mortality of the San Jose scale in fruit orchards in Emilia Romagna (Northern Italy) (Bollettino di zoologia agraria e bachicoltura, 2024)
To establish the developmental stage of overwintering San Jose Scale.Quadraspidiotus perniciosus {Comstock) (Homoptera: Diaspididae) specimens inNorthern Italy, a monitoring progran1me \Vas canied out in Emilia-Romagnaduring winter 1998-99, mainly on stone fruit. According to the data collected,most of the specimens ~pend the greatest part of the winter in the first ~tag e. Onlyin 1narch specimens begin lo develop quite quickly to\vards the second and thenthe adult stage. The natural winter mortality recorded is significant but ~o i~ thefact that important differences exist bct,,.,,een years. The importance of these datafor timing insecticide treat1nent also 1.vith IGRs and for choosing the mostsatisfactOl)" and suitable \Vinter control strategy of the pest. is discussed.
Keywords: Quadraspidiotus; perniciosus; control strategies; development